2017
DOI: 10.1177/0075424217740938
|View full text |Cite
|
Sign up to set email alerts
|

Voice Alternation and Authorial Presence: Variation across Disciplinary Areas in Academic English

Abstract: This paper examines voice alternation, that is, variation between the active and passive voice in academic Englishes. The focus is on differences regarding degrees of author involvement. A previous study on the use of be-passives in fifteen varieties of academic English (Hundt, Schneider & Seoane 2016) found voice alternation to be very similar in both contact and native (ENL) varieties of English, with only American English showing a pronounced tendency towards a more frequent use of actives. A more fine-grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…Nevertheless, in this Med-RAs corpus in particular, the uses of passive constructions outnumber those of self-mentions. As previous research shows (Seoane and Hundt 2018), passive constructions are indispensable to create objective knowledge, apparently deprived of human intervention, in academic writing in general and in medical discourse in particular. Despite the voice alternation in genres and disciplines, it is easy to unveil the agency of the research experience reported by the apparent impersonal construction of a passive structure.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, in this Med-RAs corpus in particular, the uses of passive constructions outnumber those of self-mentions. As previous research shows (Seoane and Hundt 2018), passive constructions are indispensable to create objective knowledge, apparently deprived of human intervention, in academic writing in general and in medical discourse in particular. Despite the voice alternation in genres and disciplines, it is easy to unveil the agency of the research experience reported by the apparent impersonal construction of a passive structure.…”
Section: Discussionmentioning
confidence: 96%
“…Dorgeloh & Wanner (2009) explain the use of this so-called ‘paper construction’ in academic writing – which they find is first used in the twentieth century – by pointing out specific requirements of the genre, focusing on rhetorical functions such as allowing the author to leave him/herself unmentioned. A study by Seoane & Hundt (2017) further illustrates that this choice is not just linguistic, but stylistic, with important differences between disciplines in the amount of so-called authorial involvement. Impersonalisation strategies can also be relevant for other permissive subjects; for example, 1492 saw… replaces In 1492 we/people saw… .…”
Section: Permissive Subjects In Present-day English: Definition and Ementioning
confidence: 99%
“…He argues that this process has profoundly shaped discourse, for example, by an increasing acceptance of non-standard varieties in institutional discourse, the reduction of overt markers of power, and traditionally formal discourse types becoming more informal. Since Fairclough’s work, the term has been used in various studies in different areas of linguistics without necessarily subscribing to the principles of CDA (e.g., Leech, Hundt, Mair & Smith 2009; Flowerdew 2012; Spirling 2016; Seoane & Hundt 2017). Examples of specific linguistic changes attributed to democratization include the decrease of deontic modals and the rise of semi-modals, and the elimination of overtly sexist features in language, such as generic he and occupational terms ending in – man (Farrelly & Seoane 2012:394).…”
Section: Discursive and Linguistic Democratizationmentioning
confidence: 99%